Peran Lingkungan Keluarga Dalam Pengenalan Konsep Huruf Pada Anak Usia 6 Tahun di Kober (Kelompok Bermain) Kaizan - Widaningsih, Wida; Munajat, Asep; Elnawati, Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
This study aims to find out the factors in the family environment that affect the ability to recognize letters in 6-year-old children at KOBER Kaizan and to find out how the picture of letter recognition in the family environment in 6-year-old children at KOBER Kaizan is described. The research method used in this study uses a qualitative approach using a case study research design (case study). The subjects of this study are parents and children aged 5-6 years in KOBER Kaizan. Sampling of data sources is by using purposive sampling, which is taking data sources with certain considerations. The results of the research on the role of the family in the introduction of letter concepts in 6-year-old children at KOBER Kaizan, it can be concluded that the family is interested in helping children in letter recognition by paying attention to several things, namely how to educate children, relationships between family members, the atmosphere of the home environment and the understanding of parents. The way parents educate children in knowing letters is done by reading storybooks, exemplifying children reading letters, by watching learning videos about letters. The relationship between family members in knowing letters is carried out by the grandmother introducing letters to children through the recognition of letters in food packaging during snacks, then the older brother plays guessing with his younger brother by guessing the names of animals from the alphabet, then the older brother and sister learn together. The atmosphere of the home environment when children are studying must also be calm so that children can learn calmly and conducively. Then what must be considered is the understanding of parents. Forms of parental attention can be in the form of facilities and motivation for children.